First radiation of Cretaceous planktonic foraminifera with radially elongate chambers at Angles (southeastern France) and biostratigraphic implications - R. COCCIONI; A. MARSILI; I. PREMOLI SILVA; VERGA, DAVIDE (Revue de Micropaléontologie, 2007)
The study of planktonic foraminifera from the Lower Cretaceous succession at Angles (Southeastern France) directly correlated with ammonites, confirms that the origin of morphotypes with radially elongated chambers occur earlier than previously recorded. In particular, the species Hedbergella semielongata and Hedbergella roblesae bearing subclavate to clavate chambers first appear in the upper Hauterivian, just predating the onset of the oceanic anoxic Faraoni event. Based on these observations, a new zonation is proposed.